2011
DOI: 10.1177/1010539511409392
|View full text |Cite
|
Sign up to set email alerts
|

Equity of Access to Primary Care Among Older Adults in Incheon, South Korea

Abstract: The present study examines the extent to which equity in the use of physician services for the elderly has been achieved in Incheon, Korea. It is based on the Aday and Andersen Access Framework. The results indicate that a universal health insurance system has not yielded a fully equitable distribution of services. The limitation of benefit coverage as well as high out-of-pocket payment can be a barrier to health care utilization, which results in inequity and differential medical care utilization between subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 6 publications
1
13
2
Order By: Relevance
“…Lastly, it is important to note that socio-economic factors, rather than health-related factors, have more predictive power of the use of health services. This finding is inconsistent with previous studies [13] [14], showing the opposite result. I observed a 20% -30% higher likelihood of health care utilization among individuals who have working status than those who have never had.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Lastly, it is important to note that socio-economic factors, rather than health-related factors, have more predictive power of the use of health services. This finding is inconsistent with previous studies [13] [14], showing the opposite result. I observed a 20% -30% higher likelihood of health care utilization among individuals who have working status than those who have never had.…”
Section: Resultscontrasting
confidence: 99%
“…An interesting finding in this study is the fact that people living in urban areas have significant higher utilization of specialist services than people living in rural areas. This may be related to the geographic mal-distribution of providers that may be reflected in the lower utilization of specialists in rural areas [13]. In Korea, with the government's "laissez-faire" policy for the private medical sector, more than 90% of physicians and hospital beds are concentrated in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…CHC have taken a leading role helping states and local communities plan for public health problems by supporting vulnerable populations, managing chronic disease, and providing home healthcare, rehabilitation, and health education. However, despite these efforts, previous studies concluded that South Korea continues to have disparate access to healthcare [3,4].…”
mentioning
confidence: 96%
“…Just nine studies referred explicitly to a conceptual framework that guided the analysis. For example, Litwin and Sapir [36] made reference to the Andersen-Newman model of health service utilisation [37] and Park [38] drew on the Aday and Andersen access framework [39]. …”
Section: Resultsmentioning
confidence: 99%